Escrita autobiográfica do idoso e invenção de si - Larissa Maria de Resende Neiva (2017)
The study proposes to analyze the autobiographical writing and the process of selfinvention by the elderly. Eight autobiographies were analyzed: five written by men and three written by women aged 65 and over, born in the first half of the 20th century in Minas Gerais and who wrote and / or published their works from the year 2000. Autobiographical writing as a process of constructing a narrative about itself from reference points of the moment in which writing occurs, having the memory assupport, resulting, therefore, in the invention of itself. The first chapter discusses the new configurations that aging took on from the 1960s and 1970s in Brazil, and the relationship of this phenomenon with the growing publication of autobiographical character in the country. The construction of a new conception of aging in Brazil, with the idea of a participative and accomplished elderly, coincides with the autobiographical boom in the country, constituting a favorable scenario for the publication of autobiographies of the elderly. In this context, the study sheds light ona small part of the population that, having attended the first years of primary education, in the interior of Minas Gerais in the first half of the 20th century, migrated to large urban centers and, whether attending higher levels of education , Whether by self-didatism, became and were recognized as writers, publishing their autobiographies. In the second chapter, we analyze the identity belongings chosen by the authors as the guiding axis of the reworking of the past: social, geographical, religion, work and family status. These belongings are apprehended not only from'pure' narration, but also through the analysis of some complementary resources to the narrative, such as the use of quotations, photos, documents, references to thirdparty speech, and the motivations for autobiographical writing . The analysis showed that, although dynamic, the belongings listed in the narratives by the authors are not neutral. Religion and the family appear as the guiding thread of female narratives,while professional, socioeconomic, and geographical belonging emerge as the background to the life histories of the men analyzed. Already in the third chapter, we sought to analyze the references to aging and tobeing old that appear in the works when the authors construct their narratives. It has been found that women are more adapted and accomplished at this stage of life, while discomfort and nostalgia appear as marks of men's narratives